تقييم كفاءة المقاومة الزلزالية للأبنية البيتونية المسلحة بالاعتماد على طريقة الدفع الجانبي أبنية ضاحية الطابيات السكنية في اللاذقية نموذجاً - زكائي طريفي (Tishreen University, 2016)
تعدّ طريقة الدفع الجانبي أو طريقة التحليل الستاتيكي اللاخطي من أحدث وأفضل الطرق لدراسة سلوك المباني وتقييمها بتأثير أحمال الزلازل. تعتمد الطريقة على دراسة التشوهات الحاصلة في المبنى كالانتقالات، وتشكل المفاصل اللدنة في عناصر المنشأ، بالإضافة إلى إعادة توزيع القوى الداخلية في عناصر المبنى بتأثير االحمولات الزلزالية. طبقت طريقة الدفع الجانبي  لتقييم نموذج من المباني في ضاحية الطابيات السكنية  باللاذقية والتي درست ونفذت قبل صدور الكود المتعلق باعتبار حمولة الزلازل . فحددت الخصائص الديناميكية للمبنى (دور الاهتزاز، وأنماط الاهتزاز) في حالتي النمذجة المستوية والفراغية  . وأجري ثانيا تحليل للمبنى بتأثير الحمولات الزلزالية بطريقة الدفع الجانبي اعتماداً على برنامج ETABS  ، وقد حصلنا على سبع حالات دفع جانبي للمبنى، وحددت مواقع تشكل المفاصل اللدنة في عناصر المبنى،  ورسم منحني السعة للمبنى والذي يمثل العلاقة ( قوة القص القاعدي - الانتقال الجانبي في أعلى المبنى)، وتم الاستنتاج بأن المبنى ذو مقاومة جيدة لتأثير الزلازل. تم الاستنتاج باعتماد طريقة الدفع الجانبي لتقييم المباني القائمة ودراسة سلوكها الديناميكي، وبيان مدى مقاومتها لأثر الزلازل. Pushover method or method of nonlinear static analysis is considered the latest and best way to study and evaluate the buildings under effect of seismic load.  The method is based on the study of deformation occurring in the building, formation of plastic hinge in elements, in addition to the redistribution of internal forces in building elements under the effect of earthquake loads. Pushover method was applied to evaluate the Model of residential buildings in Latakia suburb Tabiyat, who has designed and implemented before the issuance of the code which earthquake load considered. First, the dynamic characteristics of the building (Period, and Mode shape) were identified in the cases of modeling 2D (plane) and 3D (spatial). Second, an analysis of the building under earthquake load by Pushover method depending on ETABS Program  was conducted. We have got seven side cases push of the building, and have identified the location of plastic hinge in the building elements, and draw a curved capacity for the building, which represents the relationship between base shear force and lateral deflection at the top of the building. It was concluded that the building is a good resistance to the effect of earthquake. It was concluded with backing the adoption of Pushover method to evaluate existing buildings, and study the dynamic behavior, and the extent of resistance to the effect of earthquake.